Pengaruh Celebrity Endorser Terhadap Keputusan Pembelian Sepatu Specs Pada Generasi Z - Yulius Liq; Taufiq Nur Wicaksono; Awang Riko; Purnaning Dhyah Guritno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of celebrity endorsers on Generation Z's decision to purchase Specs shoes. The research method used is quantitative with a simple linear regression design. The sample consisted of 113 Generation Z respondents who are Specs shoe users, selected using purposive sampling techniques. The research instrument was developed based on five dimensions of celebrity endorsers according to Shimp (trustworthiness, expertise, attractiveness, respect, and similarity) and four dimensions of purchasing decisions according to Kotler & Armstrong (product stability, purchasing habits, recommendations, and intention to repurchase). The validity and reliability tests showed that all items in the instrument were valid and reliable. Regression analysis revealed a significance value of 0.000 (<0.05) with a coefficient of determination (R²) of 0.354. This indicates that there is a significant influence of celebrity endorsers on Generation Z's decision to purchase Specs shoes, with a contribution of 35.4%, while the remainder is influenced by other factors.